2018
DOI: 10.32674/jis.v8i2.99
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of International Student-Athletes at a Historically Black University

Abstract: The purpose of the study was to scrutinize and explain the academic, social, and athletic experiences of international student-athletes attending a historically Black university. Participants were six international studentathletes (five men and one woman). Situated in position theory, the research design was explanatory multiple case study. The primary data collection method was semi-structured interviews. The interviews were analyzed using a constant comparative approach and revealed that the participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…While these factors may have significant effects on international students' participation in on-campus activities and their overall academic success, there was a lack of demonstrated effort to factor them in to international student programming and planning; in other cases, they were underutilized Several interventions were described for higher education administrators to better serve international undergraduate students in the ever-changing campus environment. Some of the common interventions listed include: (a) facilitating regular professional development training for faculty, staff, and students to communicate regarding the significance of creating an inclusive learning environment for all (Gu et al, 2010;Lee & Rice, 2007;Poyrazli & Grahame, 2007;Rosenthal et al, 2007;Sato et al, 2018;Smith & Khawaja, 2011); (b) creating awareness of the university support services available to international students and their usefulness (Hsieh, 2007;Kenyon et al, 2012;Tsai & Wong, 2012); (c) formalizing peer support learning and mentoring for international students (Rosenthal et al, 2007); and (d) providing a broad range of content that includes multicultural elements for promoting student interactions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While these factors may have significant effects on international students' participation in on-campus activities and their overall academic success, there was a lack of demonstrated effort to factor them in to international student programming and planning; in other cases, they were underutilized Several interventions were described for higher education administrators to better serve international undergraduate students in the ever-changing campus environment. Some of the common interventions listed include: (a) facilitating regular professional development training for faculty, staff, and students to communicate regarding the significance of creating an inclusive learning environment for all (Gu et al, 2010;Lee & Rice, 2007;Poyrazli & Grahame, 2007;Rosenthal et al, 2007;Sato et al, 2018;Smith & Khawaja, 2011); (b) creating awareness of the university support services available to international students and their usefulness (Hsieh, 2007;Kenyon et al, 2012;Tsai & Wong, 2012); (c) formalizing peer support learning and mentoring for international students (Rosenthal et al, 2007); and (d) providing a broad range of content that includes multicultural elements for promoting student interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, some research reported that international students who lacked social support were negatively affected both academically and psychologically by experiences related to tension, depression, and confusion (Sato, Hodge, & Eckert, 2018;Tsai & Wong, 2012). However much international students tried, they found it challenging to establish levels of social support in their host countries that were comparable to what they enjoyed in their home countries.…”
Section: Social Experiencesmentioning
confidence: 99%
See 3 more Smart Citations